Phytobiotic role of essential oil-loaded microcapsules in improving the health parameters in Clostridium perfringens-infected broiler chickens. Issue 1 (1st January 2021) - Moharreri, Mahsa; Vakili, Reza; Oskoueian, Ehsan; Rajabzadeh, Ghadir
Abstract: Nowadays, the development of phytobiotics, an antibiotic-replacing agent, has attracted a considerable attention as poultry feed additive. The present study aims to develop the microcapsules loaded with a blend of essential oils (thyme, peppermint, savoury, and black pepper), and evaluate its health-promoting activity among the Clostridium perfringens -challenged broiler chickens. Based on the results, the spherical microcapsules containing a blend of thyme, summer savoury, peppermint, and black pepper essential oils had the particle size of 158.6 µm and encapsulation efficiency of 94.2%. The major bioactive compounds were thymol, carvacrol, p-cymene, and γ-terpinene. The microencapsulation of essential oil effectively prevented the release of bioactive phenolic compounds in the upper parts of the GIT. Additionally, it increased the delivery of the phenolic compounds to the lower segments of the GIT in the broiler chickens. The administration of the essential oil-loaded microcapsules (0.5, 1, and 2 kg/ton) in the C. perfringens -infected broiler chickens enhanced growth parameters, total feed intake, FCR, body antioxidant status, ileum morphostructure, and intestinal microbial population. Further, this treatment resulted in regulating the antioxidant and inflammation genes in ileum tissue. Consequently, the essential oil-loaded microcapsules can be considered as a promising phytobiotic against C. perfringens infection in broiler chickens. HIGHLIGHTS: The spherical microcapsules containing a blend of EO had the particle size of 158.6 µm and encapsulation efficiency of 94.2%. The microencapsulation of essential oil effectively prevented the release of bioactive phenolic compounds in the upper parts of the GIT. The EO-loaded microcapsules led to an improvement in growth parameters, body antioxidant status, ileum morphostructure, and intestinal microbial population. The microcapsules regulated the antioxidant and inflammation genes in ileum tissue.